Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

plzz answer ........

Asked by kirtichawla94 12th March 2010, 3:55 PM
Answered by Expert
Answer:

2x + 3y -7 =0        ... (1)

(m-1)x - (m+y) = (3m-1)

(m-1)x - y = 3m-1+m

(m-1)x - y = 4m-1 .... (2)

We can write equation (1),

as 2x + 3y = 7

-2x/3 - y = -7/3

Comparing with (2), coefficients of y i.e. -1 in both equations, and if other coefficients are also same, then the given pair of equations will have inifinitely many solutions.

Hence, m-1 = -2/3,

m = 1/3 or

4m - 1 = -7/3

m = -1/3.

Regards,

Team,

TopperLearning.

 

 

Answered by Expert 13th March 2010, 6:28 AM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!